Biomechanics as driver of aggregation of tethers in adherent membranes - Li, Long; Kamal, Mohammad Arif; Stumpf, Bernd Henning; Thibaudau, Franck; Sengupta, Kheya; Smith, Ana-Suncana (Soft Matter, 2021)
Cell adhesion is an important cellular process and is mediated by adhesion proteins residing on the cell membrane. Sometimes, two types of linker proteins are involved in adhesion, and they can segregate to form domains through a poorly understood size-exclusion process. We present an experimental and theoretical study of adhesion via linkers of two different sizes, realised in a mimetic model-system, based on giant unilamellar vesicles interacting with supported lipid bilayers. Here, adhesion is mediated by DNA linkers with two different lengths, but with the same binding enthalpy. We study the organisation of these linkers into domains as a function of relative fraction of long and short DNA constructs. Experimentally, we find that, irrespective of the composition, the adhesion domains are uniform with coexisting DNA bridge types, despite their relative difference in length of 9 nm. However, simulations suggest formation of nanodomains of the minority fraction at short length scales, which is below the optical resolution of the microscope. The nano-aggregation is more significant for long bridges, which are also more stable.
CRIS-Team WoS Importer:2021-11-12

Mechanical model for catch-bond-mediated cell adhesion in shear flow - Li, Long; Kang, Wei; Wang, Jizeng (International Journal of Molecular Sciences, 2020)
Catch bond, whose lifetime increases with applied tensile force, can often mediate rolling adhesion of cells in a hydrodynamic environment. However, the mechanical mechanism governing the kinetics of rolling adhesion of cells through catch-bond under shear flow is not yet clear. In this study, a mechanical model is proposed for catch-bond-mediated cell adhesion in shear flow. The stochastic reaction of bond formation and dissociation is described as a Markovian process, whereas the dynamic motion of cells follows classical analytical mechanics. The steady state of cells significantly depends on the shear rate of flow. The upper and lower critical shear rates required for cell detachment and attachment are extracted, respectively. When the shear rate increases from the lower threshold to the upper threshold, cell rolling became slower and more regular, implying the flow-enhanced adhesion phenomenon. Our results suggest that this flow-enhanced stability of rolling adhesion is attributed to the competition between stochastic reactions of bonds and dynamics of cell rolling, instead of force lengthening the lifetime of catch bonds, thereby challenging the current view in understanding the mechanism behind this flow-enhanced adhesion phenomenon. Moreover, the loading history of flow defining bistability of cell adhesion in shear flow is predicted. These theoretical predictions are verified by Monte Carlo simulations and are related to the experimental observations reported in literature.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Bistability; Catch bond; Flow-enhanced adhesion; Markovian process; Rolling adhesion; Shear rate

Molecular biomechanics controls protein mixing and segregation in adherent membranes - Li, Long; Stumpf, Bernd Henning; Smith, Ana-Suncana (International Journal of Molecular Sciences, 2021)
Cells interact with their environment by forming complex structures involving a mul-titude of proteins within assemblies in the plasma membrane. Despite the omnipresence of these assemblies, a number of questions about the correlations between the organisation of domains and the biomechanical properties of the involved proteins, namely their length, flexibility and affinity, as well as about the coupling to the elastic, fluctuating membrane, remain open. Here we address these issues by developing an effective Kinetic Monte Carlo simulation to model membrane adhesion. We apply this model to a typical experiment in which a cell binds to a functionalized solid supported bilayer and use two ligand-receptor pairs to study these couplings. We find that differences in affinity and length of proteins forming adhesive contacts result in several characteristic features in the calculated phase diagrams. One such feature is mixed states occurring even with proteins with length differences of 10 nm. Another feature are stable nanodomains with segregated proteins appearing on time scales of cell experiments, and for biologically relevant parameters. Furthermore, we show that macroscopic ring-like patterns can spontaneously form as a consequence of emergent protein fluxes. The capacity to form domains is captured by an order parameter that is founded on the virial coefficients for the membrane mediated interactions between bonds, which allow us to collapse all the data. These findings show that taking into account the role of the membrane allows us to recover a number of experimentally observed patterns. This is an important perspective in the context of explicit biological systems, which can now be studied in significant detail.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Adhesive contact; Membrane adhesion; Nanodomain; Phase space; Protein biomechanics; Receptor-ligand pairs

Molecular-scale spatio-chemical control of the activating-inhibitory signal integration in NK cells - Toledo, Esti; Le Saux, Guillaume; Edri, Avishay; Li, Long; Rosenberg, Maor; Keidar, Yossi; Bhingardive, Viraj; Radinsky, Olga; Hadad, Uzi; Di Primo, Carmelo; Buffeteau, Thierry; Smith, Ana-Suncana; et al. (Science Advances, 2021)
The role of juxtaposition of activating and inhibitory receptors in signal inhibition of cytotoxic lymphocytes remains strongly debated. The challenge lies in the lack of tools that allow simultaneous spatial manipulation of signaling molecules. To circumvent this, we produced a nanoengineered multifunctional platform with molecular-scale spatial control of ligands, which was applied to elucidate KIR2DL1-mediated inhibition of NKG2D signaling - receptors of natural killer cells. This platform was conceived by bimetallic nanodot patterning with molecular-scale registry, followed by a ternary functionalization with distinct moieties. We found that a 40-nm gap between activating and inhibitory ligands provided optimal inhibitory conditions. Supported by theoretical modeling, we interpret these findings as a consequence of the size mismatch and conformational flexibility of ligands in their spatial interaction. This highly versatile approach provides an important insight into the spatial mechanism of inhibitory immune checkpoints, which is essential for the rational design of future immunotherapies.
CRIS-Team Scopus Importer:2021-07-02

Physics of Organelle Membrane Bridging via Cytosolic Tethers is Distinct From Cell Adhesion - Kamal, Mohammad Arif; Janes, Josip Augustin; Li, Long; Thibaudau, Franck; Smith, Ana-Suncana; Sengupta, Kheya (Frontiers in Physics, 2022)
Tremendous progress has been made recently in imaging the contacts between intra-cellular organelles, which are thought to be mediated by soluble tethers. However, they are still difficult to study in cellulo, and reconstituting them in vitro is a standing challenge. Here we take a mimetic approach to study Giant unilamellar vesicles (GUVs) and supported lipid bilayers (SLBs) interacting via single- (or double-) stranded DNA sequences of two different lengths. Like intra-cellular tethers which may reside in the cytosol when unbound, the DNA-tethers are soluble, but can insert into the membrane with the help of cholesterol moieties found at their extremities. Tether-exchange between the bulk “cytosol” and the GUV/SLB membrane leads to a novel statistical ensemble in which the entire system equilibrates together, rather than individual GUVs behaving as separate closed systems. As a consequence, adhesion between the GUV and the SLB is driven by collective entropic effects amplified by tether shape changes associated with membrane bridging. A direct experimental consequence is an unusual dependence on tether-concentration, which becomes an important control parameter at low concentrations, while tether length/flexibility are less important. The establishment of this fundamentally different interaction between two membranes suggests that in physiological conditions, the regulation of contact formation inside cells may be very different from the case of the much studied ligand-receptor mediated cell adhesion.
CRIS-Team Scopus Importer:2022-02-04
Keywords: biomembranes; biomimetic systems; cell adhesion; DNA tethers; GUV; organelle bridging; tethers; vesicles

Tuning cellular uptake of nanoparticles via ligand density: Contribution of configurational entropy - Zhang, Yudie; Li, Long; Wang, Jizeng (Physical Review E, 2021)
The bioactivity of nanoparticles (NPs) crucially depends on their ability to cross biological membranes. A fundamental understanding of cell-NP interaction is hence essential to improve the performance of the NP-based biomedical applications. Although extensive studies of cellular uptake have converged upon the idea that the uptake process is mainly regulated by the elastic deformation of the cell membrane or NP, recent experimental observations indicate the ligand density as another critical factor in modulating NP uptake into cells. In this study, we propose a theoretical model of the wrapping of an elastic vesicle NP by a finite lipid membrane to depict the relevant energetic and morphological evolutions during the wrapping process driven by forming receptor-ligand bonds. In this model, the deformations of the membrane and the vesicle NP are assumed to follow the continuum Canham-Helfrich framework, whereas the change of configurational entropy of receptors is described from statistical thermodynamics. Results show that the ligand density strongly affects the binding energy and configurational entropy of free receptors, thereby altering the morphology of the vesicle-membrane system in the steady wrapping state. For the wrapping process by the finite lipid membrane, we also find that there exists optimal ligand density for the maximum wrapping degree. These predictions are consistent with relevant experimental observations reported in the literature. We have further observed that there are transitions of various wrapping phases (no wrapping, partial wrapping, and full wrapping) in terms of ligand density, membrane tension, and molecular binding energy. In particular, the ligand and receptor shortage regimes for the small and high ligand density are, respectively, identified. These results may provide guidelines for the rational design of nanocarriers for drug delivery.
CRIS-Team WoS Importer:2021-12-03